ANALISIS PENGARUH pH ALKALI TERHADAP KEKUATAN TARIK KAIN POLIESTER-KAPAS (65%-35%) PADA PENCELUPAN MENGGUNAKAN ZAT WARNA DISPERSI-REAKTIF - Krystanto Simarmata, Wendian; Mulyani, Wiwiek Eka; Cahyaningtyas, Hilmi Amanah Aditya (Politeknik STTT Bandung, 2025)
Polyester-cotton fabric was dyed using disperse and reactive dyes. Dyeing of polyester using disperse dyes is commonly performed under acidic pH condition. However, reactive dyes dyeing process requires an alkaline pH condition so that the dye can be fixed on the cotton fiber. The usage of strong alkaline can cause erosion of the surface of the polyester fiber and result in a decrease in tensile strength. This research discusses about alkaline usage in the dyeing process of polyester-cotton fabric with disperse and reactive dyes to obtain good dyeing quality without reducing the tensile strength value of the fabric. The type of alkaline used was Na 2CO3 with concentration of 10 g/L (pH 11), 15 g/L (pH 12) and 20 g/L (pH 13). The dyeing process is carried out continuously using one bath two stages (1B2S). The characterization carried out on the dyeing samples were analyzed by tensile strength testing, color strength, color evenness using spectrophotometer, and color fastness to rubbing test. The results of the research showed the best condition under pH 12 with the usage of 15 g/L Na2CO3 had greater value of 39 kg for warp tensile strength, 28.08 kg for weft tensile strength, 12.69 of color strength, 1.17 of color evenness, color fastness to wet rubbing of 4 and color fastness to dry rubbing of 4-5.